Epitheliogenesis imperfecta (Aplasia cutis congenita) concomitant with arthrogryposis in a buffalo fetus - A rare case report - Yamini, Tadipathri Munirajulu; Kumar, Neelala Revanth; Monica, Gunasekar; Rao, Kondareddy Prabhakar (Buffalo Bulletin, 2020)
The present case describes the delivery of a buffalo fetus with Epitheliogenesis Imperfecta concomitant with Arthrogryposis and its successful removal by judicious traction in a graded Murrah buffalo.